PENGARUH KINERJA PASAR MODAL ASING TERHADAP KINERJA PASAR MODAL INDONESIA - Istiono, * (Program Doktor Ilmu Ekonomi, 2008)
Globalization has facilitated fund-flows from one capital market to other capital markets, thus it has united the capital markets in all countries. The research has a goal to know the impact of foreign capital markets performance to the Indonesian capital market performance. The capital markets performance is measured by stock price indexes of each capital market during two years. The performance of all capital markets, simultaneously affect the performance of the Indonesian capital market significantly. Partially, however, only a few of foreign capital market performance affect significantly the Indonesian capital market performance. Keywords: performance, index, and capital market.